Cost Analysis of Nursing Service Activities in patients with respirator in the male internal medicine ward 1 of Songklanagarind Hospital - Juntawises, Uma; Temtap, Suthisa; Klankaew, Sukhuma; Yeesakoon, Chaveewan (Princess of Naradhiwas University Journal, 2019)
The objectives of this descriptive research were to investigate the costs of nursing service activities (unit cost) and time services for nursing activities of patients with respirator in the male internal medicine ward 1 of Songklanagarind hospital by using the Activity base cost concept. The population of this research were all 62 nursing staff members and patients with respirator in the internal medicine ward 1 between February and January 2015. The 28 patients with respirator in this study were selected by purposive sampling. The 5 instruments that used in this study consisted of 1) a form for recording the patient’s general information, 2) the nursing activities of patients with respirator dictionary, 3) an activity time observation form, 4) the summaried time spent in providing services and the number of nursing activities form, and 5) the nursing personal’s general information. All instruments were confirmed for objectivity by three experts. The content validity index of all instruments was 0.98. The interrater reliability of observation for the fourth instruments was 0.97. The data were analyzed using descriptive statistics, in term of frequency, percentage, mean and standard deviation.The objectives of this descriptive research were to investigate the costs of nursing service activities (unit cost) and time services for nursing activities of patients with respirator in the male internal medicine ward 1 of Songklanagarind hospital by using the Activity base cost concept. The population of this research were all 62 nursing staff members and patients with respirator in the internal medicine ward 1 between February and January 2015. The 28 patients with respirator in this study were selected by purposive sampling. The 5 instruments that used in this study consisted of 1) a form for recording the patient’s general information, 2) the nursing activities of patients with respirator dictionary, 3) an activity time observation form, 4) the summaried time spent in providing services and the number of nursing activities form, and 5) the nursing personal’s general information. All instruments were confirmed for objectivity by three experts. The content validity index of all instruments was 0.98. The interrater reliability of observation for the fourth instruments was 0.97. The data were analyzed using descriptive statistics, in term of frequency, percentage, mean and standard deviation. The results of the study revealed that the total cost of nursing service activities for 28 patients with respirator from admit until discharge from the hospital was THB 351,256.42, averaging THB 12,544.87 per case. The cost of key nursing service activities were divided into 4 groups, which the cost of patients with respirator nursing care was the highest, averaging THB 11,769.68 per case, followed by the cost of discharge planning, averaging THB 602.57 per case. The everage cost of preparing for admission and the admission care was THB 97.30 and THB 75.32 per case. The highest time of nursing activities was nursing care patients with respirator, averaging 2,196.95 min per case. It is suggested that nursing administrator should use this results to manage resource cost of department in order to reduce costs and improve of quality of care.